From interaction to symbol : a systems view of the evolution of signs and communication - Sadowski, Piotr, 1957- (Iconicity in language and literature, 2009)
Against the background of jargon-ridden and often obscure semiotic literature Sadowski's book offers a reader-friendly yet rigorous account of human communication and its evolution from animal and primate behaviour. What is specifically human about the way we exchange information with other people, and to what extent are our facial expressions, body language, and even emotive elements of speech still indebted to our pre-human ancestors? Why can the chimpanzees, smart as they are, not interpret animal tracks in the ground; why did religions often ban representational art; why is photography per.